Islamic Boarding School based Curriculum: Implementation at MANPK Denanyar Jombang - Muhamad Hamim Thohari; Chusnul Chotimah (SCHOOLAR: Social and Literature Study in Education, 2021)
ABSTRACT This research was conducted to provide an overview of how the pesantren-based curriculum applies in MANPK Denanyar Jombang. This research was conducted qualitatively by conducting direct and indirect data searches. Observation, interview and document search are the focus of this research. In the interview, there were at least 3 available sources, namely coaches representing caregivers from MANPK Denanyar Jombang, subject teachers and students. From the data obtained during the study, it can be concluded that MANPK Denanyar Jombang has been successful in establishing a boarding school-based curriculum. This is manifested in the attitudes of students who behave like santris but with the addition of national, technological, and religious insights and are able to contribute to society, excel in academics and non-academics, are brave and ready to appear in public, as well as critical attitudes towards the times that have become plus value for the implementation of the curriculum at MANPK Denanyar Jombang. Keywords: Curriculum, Education, Islamic Boarding School